Insolvency analysis of the food manufacturing industry in Cuenca - Orellana-Osorio, Iván; Reyes-Clavijo, Marco; Cevallos-Rodríguez, Estefanía; Tonon-Ordoñez, Luis; Pinos-Luzuriaga, Luis (UDA AKADEM, 2020)
The risk of insolvency is related to failure or business closure, for this reason the analysis and management of this type of risk is important. The insolvency risk was applied to the food manufacturing industry in Cuenca in the period 2013-2017, which allowed to determine the bankruptcy risk existing in the companies analyzed, as well as trends of the indicator in relation to the business size. Two models were applied: the business insolvency prediction model of Altman and the logistic model using the maximum likelihood method proposed by Ohlson. Altman’s model showed that companies in the 5 years analyzed are in “Safe Zone” (3,187 points in 2013 and 3,448 in 2017). Similarly, the Ohlson model, showed that in 2013 there was a 20,7% risk of insolvency in the sector, compared to 17,7% in 2017. The results of the analysis indicate that insolvency risk shows a decreasing trend in the analyzed period, which take us to the conclusion that the sector is financially healthy. However, due to the current changing environment and the internal operative management, it is very likely that the values suffer changes. Analyzing the risk of insolvency is fundamental for companies, considering that it will allow them to know the level of bankruptcy risk they have, and based on this, take measures to reduce the risk. Key words: Altman model; food sector in Cuenca; insolvency risk; Ohlson model.